'Laughing Matter': The Comic Novel in English - Lodge, David; Bradbury, Malcom (Moderna Språk, 1992)
[Introductory note: This is an abridged and edited version of a talk given by the eminent novelists and critics David Lodge and Malcom Bradbury at the 1991 Brighton International Festival. The meeting was organised by the Montpelier Society; it was chaired by John Hart, who, for the occasion, had drawn up a list of 250 humorous novels in English; thirty of the best known titles are given at the end of the talk.]